Pengaruh Intellectual Capital Dan Marketing Capability Terhadap Profitabilitas Dan Nilai Perusahaan Di Sektor Perbankan Dan Keuangan (Small Capitalization) - Raymond Putra Marwan; Sarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to examine the affect between intellectual capital and marketing capability to profitability and company’s value. The sample of the study consisted of banks and financial institution with small capitalization and listed in Indonesia Stock Exchange (IDX). Data were collected from the annual reports for the period of 2009-2014. The total number of observation was 75 firm year. The hypotheses tested by using Multiple Linear Regression. Intellectual capital measured by using each component which were human capital efficiency, structural capital efficiency, capital employed efficiency. Marketing capability measured by using marketing and R&D expenditures, while profitability measured by using Return on Assets. Company’s value measured using Tobin's q. This study used company size and age control as variables. The results of this study found that human capital efficiency, capital employed efficiency, company size were significantly associated with profitability and human capital efficiency, structural capital efficiency, company size was significantly associated with company’s value.